GENDER FEATURES OF THE POPULATION'S ATTITUDE TO MEDICINES - N. B. Dremova; N. P. Yaroshenko; N. I. Afanaseva; S. V. Solomka (Фармакоэкономика)
Objective. The study of gender features of attitudes visitors of pharmacies to medicines.Materials and Methods. Conducted sociological survey thru the original questionnaires in 2015 among pharmacy customers. The survey included 380 respondents (190 men and 190 women) living in the cities of Central Russia. During the interview, respondents were asked, among other things evaluate the 13 influencing their choice when buying of consumer qualities of medicines. For statistical analysis used the methods of variation statistics, ranking, grouping, correlation analysis.Results. We have identified the priority qualities of medicines which are essential for consumers, in particular: efficiency, minor side effects, low cost, clear information on the package, convenient medicinal form of production. We have not detected significant gender differences in the assessment of consumer qualities of medicines that led to the conclusion of equivalence of consumer attitudes of men and women to them.